Settling velocity of a porous object - Cheryl Lim Ling (2014)
Many researchers have developed new models in attempts to improve Stokes’ law and to better describe the settling of porous objects. One such model is Brinkman’s extension of Darcy’s Law (Neale, Epstein, & Nader, 1973), which has been proven effective for modelling the sedimentation of porous objects. However, it is only applicable in the limiting case of the creeping flow region, where Reynolds number is less than unity. In many industrial applications, the Reynolds number is not always less than unity thus there is a need to experiment with flows of high Reynolds number. The purpose of this project is to examine the effect of porosity on the settling characteristics of porous objects by measuring the terminal velocity experimentally. The expected outcome is to develop expressions of drag coefficient as a function of Reynolds number and porosity.